The Effect of Early Childhood Teacher's Educational Background on the Ability to Manage Children’s Learning: Evidence From Learning Process During Covid 19 Pandemic - Imtiyas, Isnaini Aulia Rofiqoh; Simatupang, Nurhenti (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2022)
Purpose – This study aims to determine the effect of the teacher’s educational background on the ability to manage Early Child learning process during the Covid-19 pandemic.Design/methods/approach – This study is a descriptive correlational study with 86 ECE teachers in the Waru District as a sample. The analysis of this research uses simple regression, and the data collection process uses a questionnaire with the Google Forms platform.Findings – The results of this study are that the educational background and teacher training positively impact teachers' ability to manage Early Childhood Education (ECE) learning during the COVID-19 pandemic. It is proven by the R Square test obtained 0.467. In addition, the more mature ECE teachers are in line with the teacher's performance in managing ECE learning. So that in general, the educational background of teachers in Waru Regency has met the qualification standards set out in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 137 of 2014 concerning National Standards for Early Childhood Education.Research implications/limitations – This study interprets that educational background, such as certificates, Linearity of education majors, and professional teachers’ certification, can affect teacher performance in learning management in early childhood education.Practical implications – This study contributes that the higher the level of ECE teachers with educational backgrounds and certificates under ECE, the more professional they are in carrying out the learning process in ECE.Originality/value – This study highlights that the quality of educator/teacher affects the ECE learning quality.Paper type: Research paper